Re-challenging pralsetinib following recovery from pneumocystis jirovecii pneumonia in a lung cancer patient: a Case Report - Zhao, Zhe; Pang, Longbin; Liu, Surui; Liu, Jie (Frontiers in Pharmacology, 2025)
BackgroundPneumocystis jirovecii pneumonia (PJP), an opportunistic infection, is commonly observed in immunocompromised individuals, particularly those with cancer, and is known for its significant morbidity and mortality rates. Pralsetinib is a highly specific inhibitor that targets advanced or metastatic non-small cell lung cancer (NSCLC) characterized by RET-fusion positivity. The incidence of PJP infection in patients receiving pralsetinib was found to be infrequent. However, there is currently a lack of consensus regarding the rechallenge of pralsetinib in patients who have fully recovered from PJP.Case presentationIn this case study, a 60-year-old patient diagnosed with stage IV lung adenocarcinoma and carrying a KIF5B-RET fusion gene underwent pralsetinib treatment as the fourth-line therapy. Subsequently, the patient developed a fever and dyspnea 2.5 months later. However, the patient did not exhibit a positive response to the empirical antibiotic therapy administered. The computed tomography findings indicated widespread ground-glass opacities with numerous cystic lesions in both lungs, along with patchy consolidations in the lower right lung. The diagnosis of PJP was conclusively confirmed through bronchoalveolar lavage. The patient’s condition was effectively treated with a combination of oral trimethoprim/sulfamethoxazole and intravenous caspofungin along with clindamycin. The patient fully recovered from PJP. Subsequently, he underwent a rechallenge with pralsetinib, and as of the latest follow-up, no evidence of progressive disease has been observed.ConclusionThis case report emphasizes the significance for physicians to be cognizant of the potential hazard of PJP development in cancer patients undergoing pralsetinib treatment, particularly in those who are unresponsive to empirical antibiotic therapy. Prompt identification and timely intervention are essential to achieve better outcomes in patients with pralsetinib-induced PJP. Furthermore, it highlights the scenario where patients who have fully recovered from moderate-to-severe pralsetinib-induced PJP may undergo pralsetinib re-administration without requiring alternative treatment options.